Pathophysiology, Diagnosis and Treatment of Tinnitus - a literature review - Piekarska, Martyna; Dąbek, Katarzyna; Ochwat, Michał; Sudoł, Maria; Mierzwa, Gabriela; Kajtel, Aleksandra; Skowronek, Anna (Journal of Education, Health and Sport, 2024)
Introduction and purpose Primary tinnitus involves the perception of various types of sounds, usually without the presence of an external or internal stimulus (we then speak of primary tinnitus). Secondary tinnitus is rare, but should be ruled out at the beginning of the diagnostic process, as it can result from a serious disease. The issue of ear noise is a widespread problem in primary care. The purpose of our article was to summarize information on tinnitus, its risk factors, pathophysiology, diagnosis and treatment. Materials and methods To write this article, databases such as PubMed and Google Scholar were searched using the following terms: tinnitus, tinnitus treatment, tinnitus cognitive behavioral therapy. Description of the state of knowledge There are many mechanisms that can lead to tinnitus. Since they often coexist with hearing loss, tinnitus is thought to be a response to sensory deprivation. In diagnosis, it is very important to take a thorough medical history to distinguish primary from secondary tinnitus, which determines further management of the patient. Due to the truncated knowledge of the pathophysiology of tinnitus, there are no clear guidelines for the treatment of tinnitus. There are various therapeutic options available, such as cognitive-behavioral therapy, sound therapy, somatosensory therapy, neuromodulation and hypnosis. They improve patients' quality of life, however, reliable data confirming reductions in tinnitus intensity is often lacking. Conclusions Tinnitus is a commonly encountered condition. Although significant research has been conducted, our understanding, particularly of its pathophysiology, remains incomplete. This makes it difficult to develop effective treatment.